2022
DOI: 10.21303/2504-5571.2022.002486
|View full text |Cite
|
Sign up to set email alerts
|

Human resource professionals and readiness for the future of work

Abstract: The current shift in the world of work, moving from a conventional to a digitalized workplace, has necessitated that professionals embrace and prepare for emerging work patterns. This study evaluates the readiness of human resource (HR) professionals for future work, given the emerging trends of the technologies of the fourth industrial revolution in Nigeria. This is particularly important because the HR professionals are responsible for the entire workforce in any organization and there are concerns that if H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In the customer support case study, agents who utilized AI tools achieved competence levels that typically took eight months in just two months. This accelerated learning highlights the potential of AI to expedite skill development and proficiency, benefiting both employees and (Jacob, 2018) (Dlamini et al, 2022), (Susilo, 2020) Employee Skills have a significant effect on employee performance Employee Skill and Human Resource Readiness (Adeosun & Adegbite, 2022) (Alqudah et al, 2022) (Zayed et al, 2022) High-performance HRM Practices are positively related to readiness for change.…”
Section: Artificial Intelligence and Employee Productivitymentioning
confidence: 93%
See 2 more Smart Citations
“…In the customer support case study, agents who utilized AI tools achieved competence levels that typically took eight months in just two months. This accelerated learning highlights the potential of AI to expedite skill development and proficiency, benefiting both employees and (Jacob, 2018) (Dlamini et al, 2022), (Susilo, 2020) Employee Skills have a significant effect on employee performance Employee Skill and Human Resource Readiness (Adeosun & Adegbite, 2022) (Alqudah et al, 2022) (Zayed et al, 2022) High-performance HRM Practices are positively related to readiness for change.…”
Section: Artificial Intelligence and Employee Productivitymentioning
confidence: 93%
“…The study conducted by (Adeosun & Adegbite, 2022) revealed that A p-value greater than 0.05 suggests that the majority of HR professionals are not normally prepared for future employment in Nigeria. Meanwhile, the study conducted by (Alqudah et al, 2022) (and Zayed et al, 2022 revealed that Highperformance HRM Practices are positively related to readiness for change.…”
Section: Employee Skill and Human Resource Readinessmentioning
confidence: 98%
See 1 more Smart Citation